Behaviour of Composite I-Beams Under Crushing and Bending Modes - Ali, Farag Abdusslam (2004)
Experimental and finite-element analyses for glass/epoxy composite I-beams were carried out to determine the effect of number of layers on load-carrying capacity and specific energy absorption. The loading modes used throughout this investigation were the axial compression,three and four point bending. The beams were fabricated from woven roving glass fibre and epoxy. The composite I-beams fabricated for axial compression tests were of 250 mm gauge length, 76 mm flange width and 125 mm web height,while the composite I-beams fabricated for three and four point bending tests were of 500 mm gauge length, 76 mm flange width and 125 mm web height.The matrix used was made of an epoxy resin (LECO 811-563-103) and a hardener (LECO 811-563-104) which were mixed at 8:1 ratio.Loading arrangements were also built to facilitate the experimental tests needed.The composite I-beams fabricated and tested were of 4, 6, 8 and 10 layers. Three samples were tested for each type and each load case. In addition,tensile samples were prepared and tested for the composite material used to evaluate the mechanical properties needed in the theoretical analysis stage of this project.Loaddisplacement results were first obtained directly for each type of samples and for each loading mode. An average, for each three similar tests,were then tabulated for the next phase of results and calculations. Experimental results obtained from this study included the first crushing load, the energy absorption and the failure modes.The first crushing load values of composite I-beams with four, six, eight and ten layers under axial compression, three and four point bending are (41.67, 69.46, 133.1 and 222.89 kN),(5.94, 11.24, 16.57 and 23.86 kN) and (8.00, 16.39, 25.08 and 35.01 kN) respectively.The specific energy absorption values of composite I-beams with four, six, eight and ten layers under axial compression are 9.79, 14.70, 33.18 and 35.88 (kJ/kg), respectively.Whereas, the energy absorption capability values of composite I-beams with four, six, eight and ten layers under three and four point bending are (235.785, 485.791, 829.500 and 1163.771 (J)) and (201.425, 422.107, 803.622 and 1006.986 (J)), respectively.Moreover, the initial crushing bending moment values of composite I-beams with four,six, eight and ten layers under three and four point bending are (0.66, 1.26, 1.86 and 2.68 (kN.m)) and (0.6, 1.23, 1.88 and 2.62 (kN.m)) respectively. On the other hand, all composite I-beams tested under axial compression fail by local buckling followed progressive crushing failure modes.Whereas, those tested under three and four point bending fail by matrix cracking followed local buckling under the loading points